A Computed Tomographic Morphometric Study of the Pediatric Occipital Bone Thickness: Implications for Pediatric Occipitocervical Fusion. Issue 20 (15th October 2015) - Wang, Yong-Li; Xu, Hong-Ming; Wang, Xiang-Yang; Li, Yao; Shen, Zhong-Hai; Zhou, Kai-Liang; Zhou, Feng; Jin, Hai-Ming; Chen, Jiao-Xiang; Kong, Qiu-Yan
Abstract : Study Design: This study is a computed tomographic-based morphometric analysis of the pediatric occipital bones as related to pediatric occipitocervical fusion. Objective: To quantify reference data concerning the thicknesses of the immature occipital bones to guide the pediatric occipitocervical fusion. Summary of Background Data: To the best of our knowledge, no published study has provided insight into the thicknesses of pediatric occiputs with different age groups. Methods: 80 pediatric patients were divided into 4 age groups, and their occiputs were studied on Philips Brilliance 256 iCT scan. Results: The mean thickness ± standard deviations of the pediatric occipital bones with different age groups is shown. The median and the paramedian regions are always thicker than the more lateral regions at each age group and the thickest point in the occiputs is mostly at the external occipital protuberance. The mean thickness of occiputs showed an obvious significant difference between each 2 age groups and no significant difference between male and female in different age groups except the group 4. Conclusion: Our investigation provides insight into the anatomy of occiputs in pediatric population and preoperative CT evaluation must be required to further decrease the risk of occipitocervical fusion. Level of Evidence: 2 Abstract : This article provided insight into the anatomical considerations of pediatric occipital bones to make indications for pediatric occipitocervical fusion. The data showed significant age-related differences about pediatric occipital bone thickness and the median region is advised as the main region of screw placement for children.